EduFarm, A Conceptual Studies: Growing Knowledge Through Urban Farming in Schools (Proceeding International Collaborative Conference on Multidisciplinary Science, 2025)
This study introduces EduFarm, an educational innovation that integrates urban farming into the learning process to enhance students’ knowledge, technical abilities, and awareness of sustainability. The initiative responds to the limitations of conventional education, particularly the lack of experiential and practical learning in many institutions, including MARA Junior Science College (MRSM). Students often experience a disconnect between academic content and real-life applications, especially in areas related to nature and sustainability. The aim of this research is to investigate how urban farming, when combined with educational technologies, can improve students’ technical and cognitive skills in alignment with the Sustainable Development Goals (SDGs). The research design includes both pre-class and in-class activities, supported by structured assessment templates for students and teachers. A key hypothesis will be tested to determine the relationship between engagement in urban farming and the development of technical and thinking competencies. Data will be analyzed using SPSS regression tools, focusing on t-values and p-values to evaluate statistical significance. It is anticipated that urban farming will positively influence both sets of skills, offering a tangible and interactive educational experience. The findings are expected to demonstrate that integrating hands-on farming practices with modern pedagogical strategies fosters more engaging, relevant, and impactful learning. Moreover, EduFarm is projected to offer a scalable and sustainable model that enhances student outcomes not only academically but also personally, by cultivating real-world problem-solving abilities and environmental responsibility. This model could serve as a transformative approach in diverse educational contexts, bridging the gap between theoretical learning and practical, life-oriented education.